RANCANG BANGUN SISTEM MONITORING KETINGGIAN SAMPAH DAN TINGKAT GAS METANA PADA BAK SAMPAH BERBASIS IoT - I Made Mudiarta; I Gusti Ngurah Janardana; I Wayan Arta Wijaya (Program Studi Teknik Elektro UNUD, 2020)
Garbage is often a problem, especially in big cities. The average amount of waste in Indonesiais 64 million tons / year, while the number of landfills in Indonesia is around 400 with a landfill capacitythat can accommodate 233 kg / day. Not to mention the unpleasant odor and dirty city views causediscomfort. This is where a solution is needed by leading to the use of technology in an effort tocreate a clean environment by reducing the level of waste accumulation and reducing waste litteredwith the Internet of Things technology. This tool is able to monitor the height of waste and gas contentvia the web. The internet system uses the MCU Node module with energy supply from solar cells.Working voltage of the control system is 5V, a stepdown module is needed to reduce the batteryvoltage from 12V to 5V. Detection of the height of waste using a PING sensor and to determine thelevels of methane gas using the sensor MQ-135. From testing at Student Center LT 4, it was foundthat the garbage accumulated on Saturday by 60 cm with 126 PPM methane gas levels that indicatedunhealthy. This monitoring system can last up to 7 days because it uses solar cells, but this canexperience changes due to the intensity of the sun.